2007
DOI: 10.1093/hmg/ddm150
|View full text |Cite
|
Sign up to set email alerts
|

The coding polymorphism T263I in TGF-β1 is associated with otosclerosis in two independent populations

Abstract: Otosclerosis is a progressive hearing loss characterized by an abnormal bone homeostasis of the otic capsule that leads to stapes fixation. Although its etiology remains unknown, otosclerosis can be considered a complex disease. Transforming growth factor-beta 1 (TGF-beta1) was chosen for a case-control association study, because of several non-genetic indications of involvement in otosclerosis. Single nucleotide polymorphism (SNP) analysis in a large Belgian-Dutch sample set gave significant results (P = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 62 publications
5
87
1
4
Order By: Relevance
“…Several studies have reported that the SNPs in the functional regions of the TGF-β1 gene, such as −509C/T, +869T/C, positions −800, codon 25, and codon 263, may affect TGF-β1 expression and production by influencing the transcriptional activity of TGF-β1, steady-state concentrations of TGF-β1 mRNA in peripheral blood mononuclear cells, and serum TGF-β1 levels [30][31][32][33]. A previous study that analyzed the TGF-β1 gene SNP at codon 10 (rs1800470) showed no association with PCOS in Korean women [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the SNPs in the functional regions of the TGF-β1 gene, such as −509C/T, +869T/C, positions −800, codon 25, and codon 263, may affect TGF-β1 expression and production by influencing the transcriptional activity of TGF-β1, steady-state concentrations of TGF-β1 mRNA in peripheral blood mononuclear cells, and serum TGF-β1 levels [30][31][32][33]. A previous study that analyzed the TGF-β1 gene SNP at codon 10 (rs1800470) showed no association with PCOS in Korean women [34].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of TGF-β1 at low levels primes osteoclast precursors for osteoclast differentiation, and at higher levels inhibits osteoclastogenesis (Karst et al, 2004). A recent case/control association study has shown that there is a variant of TGFB1 that is underrepresented in patients with otosclerosis as compared to control subjects in Belgian-Dutch and French populations (Thys et al, 2007b). Identification of an association of two bone morphogenetic proteins, BMP2 and BMP4, with otosclerosis lends additional support to a role for TGF-β signaling in the disease process (Schrauwen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Association between COL1A1 and otosclerosis has been reported although with controversial results (Chen et al, 2007;McKenna et al, 1998;Rodriguez et al, 2004). Another more robust study showed that there is an under-representation of an active variant of TGFB1 in otosclerosis patients, which may inhibit osteoclast differentiation and initiation of aberrant bone remodeling in the otic capsule (Thys et al, 2007b). Association of two bone morphogenetic proteins, BMP2 and BMP4, has also been reported (Schrauwen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For the complex form of otosclerosis, several association studies were performed to identify genes. [9][10][11][12] Many different hypotheses for the etiology of otosclerosis have been proposed, including several theories involving a role for the immune system. It has been suggested that disease pathology can be induced by an autoimmune reaction to type II collagen present in embryonic cartilaginous remnants in the endochondral layer of the otic capsule.…”
Section: Introductionmentioning
confidence: 99%